Competing for Dark Trades - Paul J. Irvine; Egle Karmaziene (Tinbergen Institute, 2023)
We use recent European restrictions to evaluate how traders substitute across available dark pools. Our findings suggest that restricting dark trading at the most prominent platform has a detrimental effect on dark trading activity. Annual dark trading in a restricted stock decreases by more than 50% over the six-month restriction period. Consistent with investors' sticky relationships with specific dark pools, our results suggest that substitution across dark pools is remarkably low. Despite the availability of alternative dark pools, traders are unwilling to trade elsewhere. Our study provides evidence that dark trading is not a market of exchanges, but rather a collection of independent silos. This fact has implications for the vulnerability of dark trading to the introduction of an HFT into the pool, and sharpens our understanding of how the pecking order theory of trading actually functions.
Keywords: G12; G14; G18; D47; 330; MiFID II; dark pool trading; competition